Finite-Time Transport Structures of Flow Fields - Shi, Kuangyu; Theisel, Holger; Weinkauf, Tino; Hege, Hans-Christian; Seidel, Hans-Peter (2008 IEEE Pacific Visualization Symposium, 2008)
Modern experimental and computational fluid mechanics are increasingly concerned with the structure nature of fluid motion. Recent research has highlighted the analysis of one transport structure which is called Lagrangian coherent structure. However, the quantity nature of the flow transport is still unclear. In this paper, we focus on the transport characteristics of physical quantities and propose an approach to visualize the finite-time transport structure of quantity advection. This is similar to an integral convolution over a scalar field along path-lines of a flow field. Applied to a well-chosen set of physical quantity fields this yields structures giving insights into the dynamical processes of the underlying flow. We demonstrate our approach on a number of test data sets.